Implementasi penerapan SMK3 dan safe place dengan metode JSA dan hirarc dalam memperkuat budaya keselamatan - Tasya Vidia Alfiani; Willia Novita Eka Rini; David Kusmawan; Silvia Mawarti Perdana (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Implementing an Occupational Safety and Health Management System (SMK3) is crucial for preventing workplace accidents and creating a safe work environment. The increasing number of workplace accidents in Indonesia indicates that implementing occupational safety remains a challenge in various sectors, including the electricity sector, which faces high risks such as electrical hazards, construction workers, and workers at heights. Purpose: To determine the implementation of SMK3 based on Government Regulation Number 50 of 2012. Method: Qualitative research with a descriptive approach. Research informants were selected using a purposive sampling technique. Data collection was conducted through in-depth interviews, observation, and document review. Data were then analyzed through data reduction, data presentation, and conclusion drawing. Results: The implementation of SMK3 at PT PLN (Persero) Sumbagteng 3 Project Implementation Unit has been running well in accordance with Government Regulation Number 50 of 2012. The establishment of OSH policies, OSH planning, implementation of OSH plans, monitoring and evaluation of OSH performance, and review and improvement of OSH performance have been carried out effectively. Furthermore, the implementation of HIRARC, Job Safety Analysis (JSA), and Safe Place has also been optimal in supporting a work safety culture. Conclusion: The implementation of the Occupational Health and Safety Management System (SMK3) at PT PLN (Persero) Sumbagteng 3 Project Implementation Unit complies with Government Regulation Number 50 of 2012, supporting the creation of a physically and psychologically safe work environment. The combined implementation of SMK3, Safe Place, JSA, and HIRARC plays a crucial role in strengthening the work safety culture and supporting a safe, healthy, and productive work environment.   Keywords: HIRARC; Job Safety Analysis; Occupational Safety and Health Management System; Occupational Safety; Safe Place.